ОБ ОДНОЙ ГЕОМЕТРИЧЕСКОЙ ВАРИАЦИОННОЙ ЗАДАЧЕ - Grinbergs, Emanuels (ЛАТВИЙСКИЙ ГОСУДАРСТВЕННЫЙ УНИВЕРСИТЕТ, УЧЕНЫЕ ЗАПИСКИ, ТОМ XX, ВЫПУСК 3. 1958 ГОДА, 1958)
This is the first article of Emanuels Grinbergs devoted to subjects in differential geometry and algebraic curves that he was dealing with before WW2, e.g., in his doctoral thesis "Osculation, superosculation and characteristic points" (1943).
PAR KĀDU ĢEOMETRISKU VARIĀCIJU PROBLĒMU
On some geometric variation task